2001
DOI: 10.1108/02621710110388965
|View full text |Cite
|
Sign up to set email alerts
|

Alternative work arrangements among professionals and managers

Abstract: This study examines part‐time work arrangements among 78 women professionals and managers to learn more about their implications for career development. Specifically, it documents the level of success of the work arrangements, their expected career implications, and the factors distinguishing less successful arrangements. Results revealed specific career development challenges unique to part‐time workers, as well as challenges common among full‐time workers. Part‐time workers already adopting a protean career … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 10 publications
0
42
0
Order By: Relevance
“…Researchers have found that participants perceived female employees with flexible or reduced work schedules as having less job-career dedication, less advancement motivation, and higher likelihood of turnover [18]. MacDermid et al [47] found that the women managers interviewed felt they had lost some promotion opportunities because of using a reduced work schedule. This negative repercussion of using a flexible work schedule was consistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 97%
“…Researchers have found that participants perceived female employees with flexible or reduced work schedules as having less job-career dedication, less advancement motivation, and higher likelihood of turnover [18]. MacDermid et al [47] found that the women managers interviewed felt they had lost some promotion opportunities because of using a reduced work schedule. This negative repercussion of using a flexible work schedule was consistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 97%
“…Patriarchal systems are still evident in 'modern' societies in variant forms (Walby, 1990) and are typically expressed through the assignment of caregiving roles mainly to women (Crompton, 2002;Tang & Cousins, 2005). These values are also reflected in a masculine employment model that requires long working hours and continuous career paths (Halford, 2006;MacDermid, Lee, Buck, & Williams, 2001) without the flexibility to combine work with caregiving roles through reduced hours, flexibility in work schedules or breaks from employment.…”
Section: Hypothesismentioning
confidence: 97%
“…Although organizations are redesigning full-time into reduced-hours options in part to meet the needs of their employees, especially women with young children, this strategy appears to need rethinking. If organizations fail to create and articulate meaningful career paths for their reduced-hours staff, then the goal of retaining these employees will be thwarted (MacDermid, Lee, Buck, & Williams, 2001). To lessen the likelihood that reduced-hours employees will react to PCVs by entertaining exit behaviours, more needs to be done to provide them with other coping strategies.…”
Section: Discussionmentioning
confidence: 99%